Unraveling the facile reproducible modeled approach for bifunctional catalytic decorated polydopamine coated sponge composite for hydrogen generation. (1st September 2022) - Tariq, Muhammad; Ali, Meesam; Li, Yali; Han, Jinli; Ning, Fandi; He, Lei; Shen, Min; Bai, Chuang; Jin, Hanqing; Zhou, Xiaochun
Summary: Continuous, flexible, and pure hydrogen (H2 ) gas supply to the portable, and compact shape proton exchange membrane fuel cells and other type of fuel cells is considered as one of the key factor to be solved for researchers. In this research study, we develop the facile strategy to synthesize the novel, multipurpose catalytic decorated polydopamine coated sponge (CDPCS) composite for continuous H2 generation for a long period of time as well as storage of solution within the composite. We explore the most efficient, light weight, hydrophilic commercial sponge, that is, wood pulp sponge (WPS), and binder, that is, polydopamine (PDA). Decoration of platinum nano particles and using of sodium borohydride solution are carried out as a case study by using as‐synthesized CDPCS. Various characterization techniques such as scanning electron microscopy, transmission electron microscopy, X‐ray diffraction, Brunauer‐Emmett‐Teller (BET) analysis and energy dispersive X‐ray (EDX) analysis are successfully employed to confirm the presence and size of nano particles and successfully coating of PDA layer. Hydrogen production performance of CDPCS with respect to different mass contents of Pt nanoparticles, molar concentration of sodium borohydride and at different temperature is investigated in this research study. An 87% yield of hydrogen generation has been achieved with 18 mg contents of Pt nano particles and 3 M concentration of sodium borohydride at room temperature. We believe that our conducted research study with respect to novel, facile, reproducible designed CDPCS based composites will be highly promising to simplify the hydrogen generation system for rapidly developed portable and wearable electronic devices. Abstract : Synthesis and performance of the novel, multiple‐purpose catalytic decorated polydopamine coated sponge composite.